2005
DOI: 10.1038/sj.eye.6701838
|View full text |Cite
|
Sign up to set email alerts
|

Computer image analysis of ultrasound biomicroscopy of primate accommodation

Abstract: Purpose To assess and correct images of the eye for movements that can confound the evaluation of the presence, direction, and magnitude of intraocular movement of the crystalline lens equator during centrally induced ciliary muscle contraction (accommodation). Methods Ultrasound biomicroscopic (UBM) video images of a cynomologus monkey crystalline lens were obtained from an independent source. The images, prior to, during, and following electrical stimulation of the Edinger-Westphal (EW) nucleus were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…It has been suggested that centripetal movements of the crystalline lens edge during accommodation are an artifact due to extraocular eye movements (Schachar and Kamangar, 2005), and that in fact the lens edge moves towards the sclera during accommodation. In this study, lens edge movements were measured from a fixed reference mark on the cornea and clearly showed a centripetal movement away from the sclera during both pharmacologically and EW stimulated accommodation, in accordance with previous studies (Croft, Glasser, Heatley, McDonald, Ebbert, Dahl, Nadkarni and Kaufman, 2006;Fincham, 1937b;Glasser, Wendt and Ostrin, 2006;Grossmann, 1903;Wilson, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that centripetal movements of the crystalline lens edge during accommodation are an artifact due to extraocular eye movements (Schachar and Kamangar, 2005), and that in fact the lens edge moves towards the sclera during accommodation. In this study, lens edge movements were measured from a fixed reference mark on the cornea and clearly showed a centripetal movement away from the sclera during both pharmacologically and EW stimulated accommodation, in accordance with previous studies (Croft, Glasser, Heatley, McDonald, Ebbert, Dahl, Nadkarni and Kaufman, 2006;Fincham, 1937b;Glasser, Wendt and Ostrin, 2006;Grossmann, 1903;Wilson, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…When the ciliary muscles contract, the zonules are released from tension, causing the lens body to become more curved, allowing the eye to focus on nearby objects (Alpern 1969;Fisher 1969;Burd et al 2002). An alternative theory of accommodation states that during accommodation, relaxing of the ciliary muscles cause the equatorial zonules to pull on the lens capsule, resulting in steepening of the central anterior region and flattening at the equator (Schachar 1992(Schachar , 1999Schachar et al 1993;Schachar & Bax 2001;Chien et al 2003;Schachar & Kamangar 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound biomicroscopy (UBM) was used to measure the radius of curvature of the convexity of the silicone that extended through the central opening of the anterior plate under conditions of cycloplegia and cyclospasm. 6,7 Ben-nun and Alió did not control for spurious eye movements relative to their imaging devices. Because it has been established that the cornea does not change shape or thickness during accommodation, 2-5 the Figure 7 from the paper by Ben-nun and Alió before (A) and after (B) the administration of pilocarpine.…”
Section: Assessing Intraocular Lens Accommodationmentioning
confidence: 98%